(untitled) (Research, Society and Development, 2021)
Objective: To describe the epidemiological profile of oral cancer patients treated at a regional referral hospital for cancer treatment in Paraná. Methods: This retrospective, cross-sectional study involved a population of 274 people with oral cancer, treated from January 2007 to January 2014. Data were collected from hospital records and supplemented with admission forms from hospital. Results: It was identified that 75.2% were male, and 81.5% were white. The average age was 59 years old, ranging from 19 to 88 years old, with greater involvement for the age group over 60 years old with 48.2% of cases. The people most affected by the disease performed activities related to agriculture (21.9%) and activities related to production of industrial goods and services (20.0%). The most prevalent histological type was squamous cell carcinoma in 90.2% of cases, followed by basal cell carcinoma (3.3%) and adenocarcinoma (2.9%). Conclusions: The most affected individuals were men, white, with an average age of 59 years, with a profession related to agriculture, with lesions located mainly on the lip.